Lessons from the junk drawer: Possibilities for sustainability in art education - Stendel, Jackie (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2022)
From planetary warming and natural disasters to pollution and community unrest, the sensorium of the climate crisis pervades our daily life. Art education has the potential to help us better understand the sensory reality of the climate crisis. However, the materials used in artistic creation are ecologically unsustainable and therefore may hinder learner’s connection to ecology. Through exploring the metaphor of the junk drawer, the author positions materials as potential teachers and, subsequently, as important parts of meaningful teaching and learning. The article explores the pedagogical impacts of different art materials while arguing that sustainable materials can lead to eco-consciousness for educators and students.